An updated comprehensive review of website evaluation studies in hospitality and tourism. Issue 1 (9th January 2017) - Sun, Sunny; Fong, Davis Ka Chio; Law, Rob; He, Shan
Abstract : Purpose: This study aims to review published articles on website evaluation in hospitality and tourism for the period of 2000-2015 to provide a comprehensive updated review, as well as to offer implications for academic researchers and industry practitioners. Design/methodology/approach: Content analysis was adopted by this study to review retrieved articles on website evaluation in hospitality and tourism. Articles were then analyzed from consumers' perspective, suppliers' perspective, and both consumers and suppliers' perspectives using a systematic approach. Findings: Major findings of this study showed that a majority of articles focused on either hospitality or tourism. Moreover, most of the articles generally discussed user interface, marketing effectiveness and website quality. However, these articles did not discuss in detail the implications of website evaluation and ignore the connections between suppliers and consumers to some extent. Research limitations/implications: This study can be used as a reference for academic researchers to extend previous frameworks and for industry practitioners to reconstruct the traditional organizational chart and implementing e-strategic management strategies, including m-marketing. Originality/value: This study updates website evaluation development in hospitality and tourism in the new millennium. The findings of this study provide significant implications for hospitality and tourism researchers and practitioners to encourage supplier-consumer engagement.